1968
DOI: 10.1161/01.cir.38.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Primary Subclavian-Axillary Vein Thrombosis

Abstract: Primary thrombosis of the subclavian-axillary vein is a condition of uncertain origin resulting in proximal arm swelling, discomfort on use, and prominence of engorged collateral veins in the upper arm and chest. The literature is reviewed and the authors' own experience with 23 patients, evaluated from 1950 through 1966, is detailed. This disorder is a clinically distinct venous complication of the neurovascular compression syndrome of the upper extremity. Contrary to the findings recorded by others, spontane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1
8

Year Published

1970
1970
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(43 citation statements)
references
References 34 publications
0
34
1
8
Order By: Relevance
“…This syndrome was first related to forced muscular abduction leading to vein compression and microtrauma of vessel intimae by the subclavius muscle or the costocoracoid ligament. In the 1970s, additional cases of UEDVT were reported that involved other contributing anatomic variations of the structures comprising the thoracic outlet, such as cervical rib, anomalous musculofascial bands, hypertrophied venous valves, or aberrant pectoralis tendons [17,18]. This entity was found to occur typically in healthy young men, within the active age group, mainly in the dominant arm.…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome was first related to forced muscular abduction leading to vein compression and microtrauma of vessel intimae by the subclavius muscle or the costocoracoid ligament. In the 1970s, additional cases of UEDVT were reported that involved other contributing anatomic variations of the structures comprising the thoracic outlet, such as cervical rib, anomalous musculofascial bands, hypertrophied venous valves, or aberrant pectoralis tendons [17,18]. This entity was found to occur typically in healthy young men, within the active age group, mainly in the dominant arm.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation has been shown to prevent clot propagation, to facilitate the maintenance of venous collaterals [31] and to prevent pulmonary embolism [32]. There is also evidence that anticoagulation is effective in preventing long-term sequelae of chronic venous insufficiency [33].…”
Section: Investigation Of Uldvtmentioning
confidence: 99%
“…3 In those cases where no obvious etiology is forthcoming, the thrombosis is thought to be preceded by an ill-defined mechanism of trauma brought on by ''effort,'' and this condition is called Paget-Schroetter syndrome. 6,11 Despite the absence of an obvious etiology, anatomic anomalies such as cervical ribs, muscular fascial bands, and hypertrophied muscles (subclavius muscle and anterior scalene muscles) have been implicated in the pathogenesis of primary DVT of the upper extremity. 7,8 The onset of symptoms can be quite variable and has been described as being between 2 days and 3 years in one series.…”
Section: Discussionmentioning
confidence: 99%